PENGARUH PERTUMBUHAN EKONOMI DAN KESEMPATAN KERJA TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN BANJAR - NABIELAH FARRASY JANNATY (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Carried out during the construction of the government sometimes does not correspond to the actual needs of the community. The pattern of government that is not based on the needs of the community mayb lead to cuts in public welfare in the area as seen from high to low Human Debelopment Index (HDI) as a benchmark. Human development is a process of development that aims to be able to have more choices, particularly in income, health and education.This research is a quantitative study using secondary data, the data used in the from of time series in 2006-20016. Analysis of data using linier regression method. The purpose of this study is to analyze how much influence the variabeles of economic growth and employment simultaneously and partly variable HDI and determine which variable most dominant influenceHDI variable.The results showed the simultaneous effect of two independent variables determinan coefficient of 0,696 (R-square). And when tested partially showing economic growth and no significant positive effect on the HDI. Employment and significant positive effect on the HDI and  the most dominant variable that has seen the work of t-count and most sig-t close to 0 (zero).Keywords :Human Development Index, Economic Growth,Employment.